A Socialised Medical Service (London : The Socialist Medical Association, 1933)
1933 1933 1930s 21 pages type of mind in the two types of doctor. It indicates that the conditions of service — the atmosphere of co-operation rather than competition — of the specialists are more favourable. A greater output of research work as well as better work generally is to be expected from the future State Practitioner working in full accord with his fellows. And because this is to be expected of him, he must be given freedom, freedom to adopt his own methods of treatment, freedom from lay interference in his medical work, freedom from too many clerical duties, which latter should be entrusted to a secretary. Facilities must also be provided to make easy the passage from one branch of the service to another for those who desire a change and show capacity for new duties. Moreover, while increasing specialisation is inevitable, it is essential to provide sufficient variety of work and duties, so that the doctor does not become a mere machine. The condition of service must be sufficiently good to attract the best men and women. We regard it as of the greatest importance that the principle of relief from excessive routine work should be accepted at the outset. Leisure is necessary if the Doctor is to have time to investigate the causes of disease or to study the advances in medicine as they occur. (B) THE HEALTH SERVICE In this section an attempt will be made to describe what in the present state of our knowledge may be considered the ideal Health Service for a country such as ours. But in discussing such a Service we must be strictly practical. We must consider what is possible as well as what is desirable and we must be sure that we are getting really good value for what is spent on the health needs of the populace. The object of the Medical Service of the future will be to put every advance of modern medical science and specialist treatment as well as skilled nursing freely within the reach of all. The Service must be so efficient and so well organised that everyone, rich and poor alike, will be ready to take advantage of it. ADMINISTRATION The Health Service of the future will be administered by local authorities, supervised by the Ministry of Health, which will have charge of all the Health Centres of the nation. The Ministry must, however, use to a much fuller extent than at present the powers that it possesses for compelling reactionary local authorities to carry out their statutory duties, and many duties that are now optional must become obligatory. The unit of local administration must be large. The ideal unit would appear to be a regional one consisting of one or more large towns with the district around each for about ten or twenty 7 292/847/1/1